Multi-analytical Approach to Oxidative Stability of Unrefined Argan, Chia, Rosa Mosqueta and Olive Oils - Leiva, Graciela Edith (2015)
Fresh, unrefined argan (AR), chia (CH), rosa mosqueta (RM) and olive (OL) oils were evaluated for thermal stability with dielectric spectroscopy, differential scanning calorimetry, peroxide values (PV) and free fatty acids (FFAs). The dielectric constant (E´), dielectric loss (E´´), and melting temperature (Tm) of the oils correlated with degree of unsaturation, with the highest static dielectric constant (εs´) for CH oil (3.311), the most unsaturated. AR and CHoils showed the highest electrical conductivities at 500 Hz (505, 230 pS/m, respectively), and CH and RM oils the lowest Tm (-41.0, -36.6°C, respectively). All oils stored at 65°C for 432 hr showed minor changes in εs´. After 180°Cfor 28 h, εs´ and ε´´ increased from 5% to 7%. Initial PVs of these oils were <3.7 mmol O2/kg, and for highly unsaturated CH oil this increased to 221 mmol O2/kg after 65°C for 432 hr. At 180°C, the FFAs increased in all oils,except AR oil. Oxidation onset temperature of the oils correlated with PVs after 65°C for 432 h (r=-0.91) and with FFAs and εs´ after 180°C for 28 hr (r=-0.81, -0.83, respectively).